Efektivitas Penggunaan Google Classroom terhadap Hasil Belajar - Madaling Madaling; Lasino Lasino; Misbahul Munir; Hermin Nainggolan; Almira Ulimaz; Pius Weraman (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study aims to examine the effectiveness of using Google Classroom on learning outcomes. This research uses literature study by searching relevant journals and articles through online databases that focus on the use of Google Classroom as a distance learning media. The results of the study show that the use of Google Classroom is effective in improving student learning outcomes. The use of Google Classroom provides many benefits, such as facilitating communication between teachers and students, speeding up the assessment process, and enriching learning material with features such as videos and images. Although there are some obstacles faced in using Google Classroom, such as limited internet access and the need for training to operate the platform, the use of Google Classroom is still considered an effective alternative in the process of distance learning. Therefore, it is necessary to improve the use of Google Classroom in the educational environment, especially during the Covid-19 pandemic, by considering several important factors such as infrastructure and teacher qualifications.